2021
DOI: 10.24925/turjaf.v9i10.1915-1920.4642
|View full text |Cite
|
Sign up to set email alerts
|

Total Phenolics, Antioxidative and Antimicrobial Activities of Some Edible Ascomycota Collected from Niğde

Abstract: Mushrooms have been used as food and medicinal purposes for centuries. In this study, some edible Ascomycota were collected in 2018 and 2019 from Niğde, Turkey. Molecular identifications of the samples were performed afterward. PCR products were sent for sequence analysis after ITS fragments were amplified with suitable primers concerning DNA isolation of samples. The obtained data were compared with the Genbank database for samples’ determination. The mushroom samples were determined to be Terfezia claveryi C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Moreover, extracts of macrofungi samples prepared with different solvents and techniques showed various levels of inhibition against pathogen microorganisms (Gücin and Dülger, 1997; Barneche et al, 2016;Fakoya Adeyemi, 2021;Canpolat et al, 2021;Soliman and El-Sayed, 2021). Antibiotic resistance developed by pathogen microorganisms is a global concern and studies on searching for novel antimicrobial agents revealed that fungal species with various bioactive compounds may constitute serious candidates (Lindequist et al, 2005;Alves et al, 2013;Akgül et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, extracts of macrofungi samples prepared with different solvents and techniques showed various levels of inhibition against pathogen microorganisms (Gücin and Dülger, 1997; Barneche et al, 2016;Fakoya Adeyemi, 2021;Canpolat et al, 2021;Soliman and El-Sayed, 2021). Antibiotic resistance developed by pathogen microorganisms is a global concern and studies on searching for novel antimicrobial agents revealed that fungal species with various bioactive compounds may constitute serious candidates (Lindequist et al, 2005;Alves et al, 2013;Akgül et al, 2016).…”
Section: Introductionmentioning
confidence: 99%